Exploring the Implementation of the Religious Education System in Vocational High Schools: Strategies and Outcomes - Eka Mustika Riantina; Abdullah Idi; Mardiah Astuti (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study evaluates the enactment of the Minister of Religion Regulation Number 16 of 2010, focusing on the management of religious education in schools, specifically at SMK Yadika Baturaja. Employing a descriptive qualitative methodology, data collection involved observation, interviews, and documentation review. The data underwent stages of reduction, display, and conclusion drawing. The findings reveal compliance with the Regulation, notably article 4, paragraphs (3) and (4), which mandate religious education based on the number of students sharing the same faith. According to these paragraphs, a minimum of 15 students sharing a religion necessitates the provision of religious education at the school, whereas fewer than 15 require collaboration with nearby schools or religious institutions. The study identifies significant obstacles, including the lack of a dedicated Religious Education Laboratory and adequate worship facilities for non-Muslim faiths. Although the implementation of religious education aligns with regulatory requirements, enhancing facilities is essential to better serve each religious community.